Computation of Energy and Tensor Product of Graphs (FULafia Journal of Science and Technology, 2026)
Graph energy has increased tremendously, and many versions of the energy have been conceived and proposed. The products of connected graphs play a vital role in the study of DNA analysis. In this paper, the adjacency energy of the tensor product, strong product, Cartesian product, and categorial product of a complete graph ???????? and a cycle graph ????????, were computed. The products ????3⊗????4, ????3⊗????3,????4⊗????4,????3⊠????4,????4⊠????4,????3×????4,????3×????3,???????????? ????4×????4 were considered. The adjacency matrix and associated eigenvalues were computed, and the relationship between the graph energies was established.
Keywords: Energy of a graph; Tensor Product; Cartesian Product; Categorial Product; Strong Product